Racism in Cuba: an analysis of issue 2/2017 of the magazine El Mar y la Montaña, in Guantánamo - Maturell Ruiz, Mariurka; Smith , Lisandro René Duvergel (Universidade de São Paulo - Programa de Pós-graduação em Integração da América Latina, 2021)
Analyzing the narratives of the publications on racism and racial discrimination in issue 2/2017 of the Magazine El Mar y la Montaña de Guantánamo exposes the relevance and actuality of these debates in Cuba. In the same way, the publications in the magazine bring us closer to the hidden and / or little explored gaps of the racial issue in the Cuban social reality, through the topics: anti-Cuban subversion; Afro-feminist thought and discourse; the debate around the term Afro-Cuban; the African presence; racial issues in Rastafarian culture and advances and setbacks in the fight against racism. The racial issue, in Cuba, still causes inconveniences and causes heated positioning, because of the invisibility that was created, for decades, around it. This is due, among other reasons, to a revolutionary idealism that considered “the racial problem” resolved, by conceiving a policy of social equality that from the class point of view granted the same rights and duties without distinction of race or gender to all people. Starting from these questions, the categories racism and racial discrimination are investigated, through the analysis of the publications of number 2/2017 of the Magazine El Mar y la Montaña. For this, the Content Analysis method was used.